Guillain-Barré Syndrome due to CMV Reactivation after Cardiac Transplantation - Christina Maria Steger; Herwig Antretter; Daniel Höfer (Case Reports in Cardiology)
A 40-year-old male patient suffered from end-stage heart failure due to ischemic cardiomyopathy and received orthotopiccardiac transplantation in June 2005. The instantaneous postoperative course was uneventful, but, seven months later, he suffered from paralysis in the lower extremities finally resulting in quadriplegia and was admitted to hospital. After laboratory testings the diagnosis of a Guillain-Barré syndrome due to cytomegalovirus reactivation was confirmed.